Synthesis and Characterization of Alginate/PVA/Fe3O4 as an Adsorbent for p-Nitrophenol Adsorption - Vikandari, Sonya Nurizki; Fitriana, Fina Ahmad; Setiawati, Nia; Azizia, Negi Rahmah (Chempublish Journal, 2026)
p-nitrophenol (PNP) is one of the priority pollutants in the environment because PNP has toxic properties and is a persistent organic pollutant (POPs), so it requires more attention in waste treatment to maintain human health and aquatic ecosystems. Adsorption is one of the pollutant removal method that has the advantage of being simple and low-cost. The adsorption process involves an adsorbent that attracts and retains certain molecules, ions, and particles on its surface. Alginate is one of the biosorbents that can be used to adsorb liquid waste, but alginate has weak mechanical properties, so it can be modified with polyvinyl alcohol (PVA) to form a beads adsorbent. The addition of magnetic Fe3O4 to the adsorbent aims to provide magnetic properties to facilitate the separation of the adsorbent from the analyte. The adsorbent has been characterized using Fourier Transform Infra Red Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD), and Delsa™ Nano C Particle Analyzer. The adsorption of PNP using 0.1 gram of adsorbent using the batch method reached optimum conditions at pH 6 and a contact time of 120 minutes. The PNP adsorption process followed a pseudo-second-order adsorption kinetics model with a maximum adsorption capacity of 3.598 mg/g